(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
Gendered and sexualized torture was a specific type of torment applied to militants during the recent dictatorships in Chile and Uruguay, framed in relation to longer-term gender violence and a National Security Doctrine policy aiming to correct, discipline and model bodies as part of dictatorial control devices. We are interested in understanding this violence from a feminist perspec- tive in the context of dictatorial repressions and prioritizing subtle forms of abuse that show that these were not only sexual but gender abuses more broadly. To this end, we draw on testimonies from Chilean MIR activists and the Uruguayan MLN-T who had been detained. They embodied the greatest transgressions to the place women were supposed to occupy according to their gender, and were brutally punished as a result.